2017
DOI: 10.3310/hta21020
|View full text |Cite|
|
Sign up to set email alerts
|

Canagliflozin, dapagliflozin and empagliflozin monotherapy for treating type 2 diabetes: systematic review and economic evaluation

Abstract: Background Most people with type 2 diabetes are overweight, so initial treatment is aimed at reducing weight and increasing physical activity. Even modest weight loss can improve control of blood glucose. If drug treatment is necessary, the drug of first choice is metformin. However, some people cannot tolerate metformin, which causes diarrhoea in about 10%, and it cannot be used in people with renal impairment. This review appraises three of the newest class of drugs for monotherapy when met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 251 publications
1
48
2
3
Order By: Relevance
“…Moreover, GTI episodes (odds ratios [OR] 4–6) are reported to be higher with SGLT2i compared to placebo [ 44 ]. Recently, a systematic review and NMA by Johnston et al reported that SGLT2i as monotherapy significantly improved glycaemic parameters, induced weight loss, and reduced BP [ 45 ]. All RCTs included in this study were of ≥ 24 weeks.…”
Section: Sglt2i and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, GTI episodes (odds ratios [OR] 4–6) are reported to be higher with SGLT2i compared to placebo [ 44 ]. Recently, a systematic review and NMA by Johnston et al reported that SGLT2i as monotherapy significantly improved glycaemic parameters, induced weight loss, and reduced BP [ 45 ]. All RCTs included in this study were of ≥ 24 weeks.…”
Section: Sglt2i and Diabetesmentioning
confidence: 99%
“…All RCTs included in this study were of ≥ 24 weeks. Compared to placebo or active comparator, SGLT2i reduced A1C ( P < 0.001), body weight ( P < 0.001), lipid level ( P < 0.01), and BP ( P < 0.001) in patients with T2DM [ 45 ]. All RCTs reported a 4–9% increase in urinary tract infections (UTIs) and GTIs with SGLT2i treatment mainly in women.…”
Section: Sglt2i and Diabetesmentioning
confidence: 99%
“…This evidence synthesis represents the first published NMA that compares the effectiveness and safety of ertugliflozin to other SGLT2is. Previous NMAs of the SGLT2i class conducted prior to the availability of ertugliflozin suggested differences in effectiveness, generally favoring canagliflozin [ 11 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was excluded initially as the low threshold of HbA1c for inclusion was 6.5% HbA1c, versus our inclusion criteria of ≥ 7.0%. However, despite potential heterogeneity previous SGLT2i NMAs have included this study, and therefore a sensitivity analysis was considered appropriate [ 23 , 24 ]. In the second sensitivity analysis, studies that were not linked to the network via a common comparator (placebo) arm (Hadjadj [ 25 ]; Lewin [ 26 ]; Rosenstock [ 27 ]) were dropped from the network and analyses run.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is common practice to adapt clinical trial data from multinational cohorts to country-specific analyses, with this methodology found throughout the published literature. 45,46,[50][51][52] Moreover, the effect of IDegLira and BBT would not be expected to vary across the different country settings included in the DUAL VII trial and the UK.…”
Section: Discussionmentioning
confidence: 99%